PREDICTIVE VALUE OF CARDIAC CACHEXIA IN CHRONIC HEART FAILURE - E. S. Drobysheva; R. E. Tokmachev; A. V. Budnevsky; A. Ya. Kravchenko (Кардиоваскулярная терапия и профилактика, 2016)
Regardless  current achievements  of medicine, chronic heart  failure (CHF) is  still the  leading  cause   of  cardiovascular  morbidity and mortality.  A   special  cohort   in  CHF mortality  are   patients  with progressive body mass loss. Recently the assessment of cachexia is restricted  only with the  tests  revealing present  atrophy,  but not to predict it. Therefore, of the most significant investigation directions is search   for  reliable  biomarkers  of  early  diagnostics   and  efficacy assessment. The article focuses  on the main biomarkers having potential  prediction  value and  recommended for cardiac  cachexia assessment.